NILAI PERUSAHAAN PADA PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BEI - REGI MUZIO PONZIANI; RISMA AZIZAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to obtain an empirical evidenceabout the factors that affect firm value in nonfinancial companies. Independent variables used in this research are financial leverage, firm size, profitability, earnings per share, intangible asset, audit committee, insider holdings, and industry. This research used companies listed in nonfinancial sector in Indonesia Stock Exchange during 2013-2015. There are 86 companies meet the criteria by using purposive sampling method. The model used in this research is multiple regression analysis with IBM SPSS Version 21. The result shows that return on assets and earnings per sharehave influence toward firm value. Financial leverage, firm Size, intangible asset, audit committee, insider holdings, and industry have no influence toward firm value.